Fast neutrons Al-Hamdani utilization to solar cells performance (Baghdad Science Journal, 2005)
Been in this gravel study the effect of Alchgag fast neutrons emitted by the source on the electrical properties of silicon solar cells monounsaturated crystal at a constant rate of neutron flow rate of a wide range of neutron flow speed ranges for periods of time ranging from 2-10 hours